Excitonic channels from bio-inspired templated supramolecular assembly of J-aggregate nanowires. Issue 14 (27th March 2019) - Anantharaman, Surendra B.; Messmer, Daniel; Sadeghpour, Amin; Salentinig, Stefan; Nüesch, Frank; Heier, Jakob
Abstract : High quality J-aggregate nanowires obtained from complexation of dendronized polymers with J-aggregates. Abstract : Supramolecular assemblies with controlled morphology are of paramount importance for energy transport in organic semiconductors. Despite considerable freedom in molecular design, the preparation of dyes that form one dimensional J-aggregates is challenging. Here, we demonstrate a simple and effective route to functionalize dendronized polymers (DPs) with J-aggregates to construct tubular DP/J-aggregate nanowires. When J-aggregates are adsorbed onto DPs anchored to glass substrates, they assemble into microcrystalline domains typical for J-aggregates adsorbed on functionalized surfaces. Differently, the complexation between the dendronized polymer and J-aggregates in solution leads to dense packing of J-aggregate strands on the periphery of the DPs. Using a layer-by-layer (LBL) technique, DPs loaded with J-aggregates can also be adsorbed onto a DP monolayer. In this case, the thin film absorption spectra are narrower and indicate higher ratios of J-aggregate to monomer and dimer absorption than bare J-aggregates deposited similarly. The demonstration of J-aggregate adsorption on filamentous polymeric templates is a promising step toward artificial 1D light harvesting antennas, with potential applications in opto-electronic devices.